Biologically influenced gas fluxes revealed by high‐resolution monitoring of unsaturated soil columns - Alibert, C. (2020)
These modulations are controlled by (a) barometric pressure, (b) water content and distribution, and (c) plant metabolism. All three mainly act on the pressure gradient. Surface gas fluxes decrease under drying conditions, which increases gas porosity and the relative gas permeability and lowers the pressure gradient. Respiration of plant roots is shown to be responsible for daytime–nighttime oscillations of the tracer flux. During nighttime, O2 consumption and CO2 production locally lowers the pressure gradient up to the root zone due to the higher solubility of CO2 in pore water, resulting in an increased SF6 flux at the surface. During daytime, enhanced water loss by evapotranspiration associated with photosynthesis dominated the respiration effect and resulted in decreasing surface gas fluxes, as generally shown for drying conditions. Surface gas fluxes are therefore controlled by combined physical, chemical, and biological processes. This has important consequences, notably when discrete flux measurements are integrated in space and/or in time to quantify emissions or when used for detecting, identifying, or monitoring underground gas sources.